Phase Space Analysis of Relaxation Dynamics of Isoscalar Giant Monopole Resonances - Papachristou, P. K.; Mavrommatis, E.; Constantoudis, V.; Diakonos, F. Κ.; Wambach, J. (HNPS Advances in Nuclear Physics, 2019)
A classical model based on the independent particle approach to the nuclear dynamics is used to study the influence of the phase space structures on the onebody dissipation of isoscalar Giant Monopole Resonances. The model consists of a harmonic oscillator describing the collective excitation coupled with a nonlinear (Woods-Saxon) oscillator representing the motion of each nucléon. We are particulary interested in the dependence of relaxation on the energy of the system. We have found that in a rather broad region of parameter space, contrary to the common expectation, both Lyapunov exponent and relaxation time increase as a function of the total energy. We examine the conditions required for this effect to occur and demonstrate the key role of the dispersion relation of the nonlinear oscillator.